Magnetic adsorbents for the recovery of precious metals from leach solutions and wastewater - Aghaei, E.; Alorro, Richard; Encila, A.; Yoo, Kyoungkeun (MDPI AG, 2017)
Precious metals which include the platinum group, gold, and silver, play indispensable roles in high technology industries of the modern world due to their outstanding physical and chemical properties. As a result of diminishing availability of mineral sources, increasing demand, and environmental concerns, the recovery of precious metals from both leaching and industrial waste solutions is becoming a very important technology. Magnetic solid phase extraction (MSPE) is a technique that has received substantial consideration in the separation and recovery of precious metals because of the many advantages it offers compared to conventional methods. This technique is based on the extraction of different analytes from solutions using solid adsorbents with magnetic properties. This review focuses on different types of magnetic adsorbents, the main procedures used for synthesis, characterization and their application in precious metals recovery based on recently published literatures.